SEARCH METHOD OF ASSOCIATIVE RULES USING STRONG ITEMSETS AND FP-TREE - Krakovetskiy, Alexandr (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents strong itemsets conception which solves the problem of a huge number of candidates generation in solving the task of knowledge search in the kind of associative rules. It had been suggested the search method of strong itemsets which do not intersect as well as the search method of associative rules on the basis on strong itemsets.